2016
DOI: 10.1038/nm.4246
|View full text |Cite|
|
Sign up to set email alerts
|

Resting-state connectivity biomarkers define neurophysiological subtypes of depression

Abstract: Biomarkers have transformed modern medicine but remain largely elusive in psychiatry, partly because there is a weak correspondence between diagnostic labels and their neurobiological substrates. Like other neuropsychiatric disorders, depression is not a unitary disease, but rather a heterogeneous syndrome that encompasses varied, co-occurring symptoms and divergent responses to treatment. By using functional magnetic resonance imaging (fMRI) in a large multisite sample (n = 1,188), we show here that patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
1,404
2
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,755 publications
(1,466 citation statements)
references
References 72 publications
47
1,404
2
13
Order By: Relevance
“…Relating behavioral assessments to brain images helps grounding inter-individual vari-5 ability in anatomical and functional aspects of brain organization (Dubois and Adolphs, 2016;Abi-Dargham and Horga, 2016). The corresponding imaging-based biomarkers can then serve as intermediate phenotypes, or neurophenotypes to characterize the subjects (Drysdale et al, 2016). In this context, 10 recent years have witnessed the emergence of large-scale neuroimaging studies with rich assessments of subjects' traits and multiple brain-imaging modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Relating behavioral assessments to brain images helps grounding inter-individual vari-5 ability in anatomical and functional aspects of brain organization (Dubois and Adolphs, 2016;Abi-Dargham and Horga, 2016). The corresponding imaging-based biomarkers can then serve as intermediate phenotypes, or neurophenotypes to characterize the subjects (Drysdale et al, 2016). In this context, 10 recent years have witnessed the emergence of large-scale neuroimaging studies with rich assessments of subjects' traits and multiple brain-imaging modalities.…”
Section: Introductionmentioning
confidence: 99%
“…31 The combination of symptoms plus connectivity patterns predicted responses to rTMS better than either feature alone. 10 As anticipated, the tentatively identified biomarkers do not map on to conventional diagnostic categories. 1,32 For example, Drysdale and colleagues 10 replicated the anxietyinsomnia-related depression biotype in patients with diagnoses of generalized anxiety disorder.…”
Section: What Next?mentioning
confidence: 77%
“…10 As anticipated, the tentatively identified biomarkers do not map on to conventional diagnostic categories. 1,32 For example, Drysdale and colleagues 10 replicated the anxietyinsomnia-related depression biotype in patients with diagnoses of generalized anxiety disorder. The studies by Sheffield and colleagues [20][21][22] found the same psychosis-related connectivity patterns, irrespective of whether the patient's formal diagnosis was schizophrenia, schizoaffective disorder, or a bipolar mood disorder.…”
Section: What Next?mentioning
confidence: 77%
See 2 more Smart Citations